2016
DOI: 10.1088/1674-1056/25/7/077501
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Rashba effect and spin Hall effect in perpendicular Pt/Co/MgO magnetic multilayers

Abstract: The interplay of the Rashba effect and the spin Hall effect originating from current induced spin-orbit coupling was investigated in the as-deposited and annealed Pt/Co/MgO stacks with perpendicular magnetic anisotropy. The above two effects were analyzed based on Hall measurements under external magnetic fields longitudinal and vertical to dc current, respectively. The coercive field as a function of dc current in vertical mode with only the Rashba effect involved decreases due to thermal annealing. Meanwhile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…[6,13] On the other hand, recently, Novakov et al demonstrated that insertion of up to two monolayers of WSe 2 is able to enhance the spin transfer torques in a Rashba system by up to 3 times, [25] indicating that low layer count 2D vdW materials can be used as an interfacial scattering promoter in heterostructure interfaces without quenching the original polarization. Although there is absent of direct evidences whether MoTe 2 fits the Rashba system or not, [26] the increased scattering will enhance the spin fluctuation at the interface as well, which amplifies the spin current transmission between Pt and Ni and then improve the SOT efficiency in Pt/MoTe 2 /Ni device. [27,28] Figure 2(d) shows the linear relationships between ∆H and f , which are well fitted with the equation ∆H = ∆H 0 + 2π f α/γ, [29] where α is the Gilbert damping of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…[6,13] On the other hand, recently, Novakov et al demonstrated that insertion of up to two monolayers of WSe 2 is able to enhance the spin transfer torques in a Rashba system by up to 3 times, [25] indicating that low layer count 2D vdW materials can be used as an interfacial scattering promoter in heterostructure interfaces without quenching the original polarization. Although there is absent of direct evidences whether MoTe 2 fits the Rashba system or not, [26] the increased scattering will enhance the spin fluctuation at the interface as well, which amplifies the spin current transmission between Pt and Ni and then improve the SOT efficiency in Pt/MoTe 2 /Ni device. [27,28] Figure 2(d) shows the linear relationships between ∆H and f , which are well fitted with the equation ∆H = ∆H 0 + 2π f α/γ, [29] where α is the Gilbert damping of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of SOTs originates from the orbital angular momentum transferred from the lattice to the spin system due to the spin-orbit interaction in the HM with strong bulk spin-orbit coupling (SOC) or/and at the HM/FM interface with strong interfacial spin-orbit coupling. The former is generally described as the spin Hall effect (SHE), and the latter is commonly known as the interfacial Rashba-Edelstein effect (IREE) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The former is generally described as the spin Hall effect (SHE), and the latter is commonly known as the interfacial Rashba-Edelstein effect (IREE). [15] As shown in Fig. 1(a), SHE/IREEgenerated in-plane (IP) transverse polarization 𝜎 y spin currents exert two types of SOTs on the magnetization 𝑚 of the adjacent FM layer: one is the IP damping-like (DL) torque [1,16] 𝜏 DL = τ DL 𝑚 × (𝜎 × 𝑚); and the other is the outof-plane (OP) field-like (FL) torque [17] 𝜏 FL = τ FL (𝜎 × 𝑚).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This control has been more efficiently realized by the current-induced spin-orbit torques (SOTs) [1][2][3] than the conventional spin-transfer torques, [4,5] whereby the strong spin-orbit coupling (SOC) of a heavy metal (HM) transfers the carrier momentum directly to the local magnetization of the ferromagnet (FM). [6][7][8] Indeed, in an FM/HM bilayer or an oxide/FM/HM heterostructure, [10][11][12][13][14][15][16][17] the spin current produced by the spin-orbit effect applies a torque on the magnetization. This torque can excite or reverse the magnetization direction, hence it is expected to be applied in the magnetic memories, logic and data-storage devices.…”
Section: Introductionmentioning
confidence: 99%